التخطيط لبرامج التكوين المهنى وعلاقته بالتشغيل دراسة ميدانية بالمعهد المتخصص للتكوين المهنى سمعى نوار احمد سوق اهراس - جلاب بسمة; شابي نزيهة (My University, 2018)
Study Summary Following the development witnessed by vocational training, including an increase in the number of training institutions and the emergence of vocational education, which is considered an important step towards increasing alignment between the specializations planned for vocational training programs and job requirements, along with a set of laws, procedures, and strategies adopted to increase this alignment, vocational training plays a fundamental role in developing human resources and graduating a qualified workforce. Therefore, this study aims to develop vocational training programs to be more effective in developing individuals' capabilities and assisting them in integrating into the labor market. We chose the vocational training center as the field of field study, given the availability of a number of objective reasons, which were the primary motivation for choosing this topic, the most important of which are: - A renewable topic due to the scientific changes occurring in various training specializations. - The availability of scientific references on the phenomenon in question. - Human Resources Management - The inclusion of the research problem within the field of communication and information technology - The successful role of training in raising the competencies and capabilities of individuals, thus improving the efficiency of service institutions and production. -------------------------------- ملخص الدراسة بعد التطور الذي شهده التكوين المهني من زيادة في عدد المؤسسات التكوينية وظهور التعليم المهني والذي يعتبر خطوة مهمة لزيادة الموائمة بين التخصصات المخطط لها في برامج التكوين المهني ومتطلبات الشغل إلى جانب جملة من القوانين والإجراءات والإستراتيجيات المتبعة للزيادة من هذه الموائمة فالتكوين المهني يلعب دورا أساسيا في تنمية الموارد البشرية وتخريج اليد العاملة المؤهلة ، ونظرا لهذا جاءت هذه الدراسة لإعداد برامج التكوين المهني لتكون أكثر فعالية لتنمية قدرات الأفراد ومساعدتهم في الاندماج في سوق العمل فقد إتخذنا من مركز التكوين المهني مجالا للدراسة الميدانية ، وذلك نظرا لتوفر جملة من الأسباب الموضوعية و التي كانت الدافع الأساسي لإختيار هذا الموضوع والتي من أهمها : - موضوع متجدد نظرا للمتغيرات العلمية التي تحصل في مختلف تخصصات التكوينية . - توفر المراجع العلمية حول الظاهرة المعنية ٕ - دارة الموارد البشرية إندراج المشكلة البحثية ضمن تخصص إتصال وا - الدور الناجح للتكوين في رفع كفاءات وقدرات الأفراد وبالتالي تحسين كفاءة المؤسسة الخدماتية والإنتاجية
Keywords: التخطيط، برامج التكوين المهنى، التشغيل